A new congestion management mechanism for next generation routers - M. Kadhum, Mohammed; Hassan, Suhaidi (School of Engineering, Taylor’s University College, 2008)
While computer networks go towards dealing with varied traffic types with different service requirements, there is a necessity for modern network control mechanisms that can control the network traffic to meet the users' service requirements. Optimizing the network utilization by improving the network performance can help to accommodate more users and thus increase operators’profits. Controlling the congestion at the gateway leads to better performance of the network. Sending congestion signal sooner can be of great benefit to the TCP connection. In this paper, we propose Fast Congestion Notification (FCN)mechanism which is a new method for managing the gateway queues and fast sending of congestion signal to the sender. We tested our mechanism on Explicit Congestion Notification (ECN) packets which have higher priority; we achieved good results in terms of faster congestion signal propagation and better network utilization. Our analysis and simulations results show that the use of FCN over TCP connections sharing one bottleneck can improve the throughput, having less loss, less delay time, and better network utilization.